2023
DOI: 10.1186/s12871-023-02212-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between early blood urea nitrogen-to-albumin ratio and one-year post-hospital mortality in critically ill surgical patients: a propensity score-matched study

Abstract: Background Blood urea nitrogen to albumin ratio (BAR) is increasingly recognized as an early predictor for short-term outcomes in critically ill patients, but the association of BAR with long-term outcomes in critically ill surgical patients remains underexplored. Methods We enrolled consecutive patients who were admitted to surgical intensive care units (ICUs) at Taichung Veterans General Hospital between 2015 and 2020, and the dates of death were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Herein, the BAR further amplifies the predictive value of urea nitrogen and albumin in trauma as well as acute and critical illnesses [30]. Furthermore, BAR has been demonstrated as a reliable predictor of mortality in elderly emergency patients [31] and post-surgical patients [7,32]. Additionally, its efficacy in forecasting the prognosis of patients undergoing cardiac transplants [33], those affected by COVID-19 [34], and individuals with acute ischemic stroke [35], has been confirmed.…”
Section: Discussionmentioning
confidence: 81%
“…Herein, the BAR further amplifies the predictive value of urea nitrogen and albumin in trauma as well as acute and critical illnesses [30]. Furthermore, BAR has been demonstrated as a reliable predictor of mortality in elderly emergency patients [31] and post-surgical patients [7,32]. Additionally, its efficacy in forecasting the prognosis of patients undergoing cardiac transplants [33], those affected by COVID-19 [34], and individuals with acute ischemic stroke [35], has been confirmed.…”
Section: Discussionmentioning
confidence: 81%
“…Albumin also plays a crucial role in maintaining colloid osmotic pressure and endothelial integrity as well as in regulating inflammation and immune function 11 , 12 . Previous studies have reported that elevated BUN and decreased albumin levels are closely associated with adverse outcomes in critically ill patients 13 15 . Several studies have validated the clinical significance of the blood urea nitrogen to albumin ratio (BAR) in predicting the prognosis of sepsis, severe pneumonia, and other diseases 16 , 17 .…”
Section: Introductionmentioning
confidence: 98%
“…Albumin also plays a crucial role in maintaining colloid osmotic pressure and endothelial integrity as well as in regulating in ammation and immune function [11,12]. Previous studies have reported that elevated BUN and decreased albumin levels are closely associated with adverse outcomes in critically ill patients [13,14,15]. Several studies have validated the clinical signi cance of the blood urea nitrogen to albumin ratio (BAR) in predicting the prognosis of sepsis, severe pneumonia, and other diseases [16,17].…”
Section: Introductionmentioning
confidence: 99%